Effect of polyoxymethylene dimethyl ethers and gasoline addition in diesel on the spray and combustion characteristics in a constant volume chamber - Jingjing He; Hao Chen; Peng Zhang (Fuel Processing Technology)
PODE and gasoline are considered as the representative additives of diesel with high oxygen-containing and high volatility. And the optimal blending volume ratio of PODE and gasoline in diesel are 20 %. A CVC test bench is employed to investigate the effects of adding PODE and gasoline in diesel on the spray and combustion characteristics in this study. The spray and combustion experiments are performed under the injection pressures of 100 MPa, 120 MPa and 140 MPa. And the results show that blending PODE and gasoline in diesel can effectively improve the quality of spray atomization. Compared with D100, D80G20, D80P20 and D80G10P10 reduce the maximum improvement of SPA by 65.3 %, 85.7 % and 76.7 % respectively. The ability to improve fuel spray quality by blending gasoline and PODE decreases with the increase of injection pressure. The ability of gasoline to reduce soot emission is superior to PODE. Due to the advantages of both gasoline and PODE, D80G10P10 has the lowest total KL and time integrated natural fame luminosity among the four fuels.